(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
GirishKarnad one of the famous bi-lingual screenwriter of post-freedom India,possessed an extremely noticeable place in Indian English Literature. GirishKarnad was conceived on May 19 1938 in Matheran close Bombay. He has the force of revising andsanctioning plays with a flavour of Indian Tradition. He holds the dialectexceptionally tight to his musing as the characters are sure to tie. As abilingual playwright he has stamped a turning point in both the dialects(Kannada and English). As far as topic and fight of his plays Girish Karnadinserts his roots in the Indian soil and outlines his sensational creativeability. It is awful that the custom of Indo–english dramatization earned leastbasic consideration. The significance of Girish Karnad lays the victory on thestage and around the book fans. The utilization of society components is one ofthe purposes for Karnad’s triumph as a dramatist.